Study of machining parameters of surface roughness in electro discharge machining of tool steel - Zairul Ezree , Mohd Yunus (2008)
This thesis presents the study of machining parameters on surface roughness in Electro Discharge Machining (EDM) of tool steel. The operation of EDM is based on removing material from the workpiece by a series of repeated electrical discharges, produced by electric pulse generators at short interval, between an electrode and workpiece that being machine in dielectric fluid medium. The Full Factorial Design of Experiment (DOE) from software STATISTICA was used to formulate the experiment layout, to analyze the effect of each parameter on the machining characteristic, and to predict the optimal choices for each EDM parameters. The selected EDM parameters were Peak Current, IP (8 and 16 A), Pulse ON-time (2 and 24 µs), Pulse OFF-time (2 and 3 µs) and Servo Voltage, SV (30 and 40 V). Machining is performed on EDM Sodick AQ55L model. The Surface Roughness Tester Series Mahrsurf XR 20 is used to measure Ra. From the analysis by Full Factorial DOE, it shows that Peak Current and Pulse ON-time have significant effect to surface roughness. The analysis also determined the optimum condition of the machining parameter. The lower values of these parameters the lower surface roughness. The confirmation tests and comparison test were performed for the optimum condition for the machining characteristic. The result of comparison tests showed that the percentage of performed is not accurate but this result can be accepted because the error percentage is below 10%.